2008
DOI: 10.2337/dc07-2188
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Pattern of Antibiotic Prescription Profile and Recurrence Rate for Possible Urinary Tract Infections in Women With and Without Diabetes

Abstract: OBJECTIVE -Women with diabetes have a high incidence and complication rate of urinary tract infections (UTIs). Our aims were to compare current treatment strategies with respect to recurrence rates in women with diabetes with those without diabetes.RESEARCH DESIGN AND METHODS -We used a Dutch registration database containing pharmacy dispensing data. A total of 10,366 women with diabetes (17.5% premenopausal) (aged Յ55 years) and 200,258 women without diabetes (68% premenopausal) who received a first course of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 19 publications
3
32
1
Order By: Relevance
“…Anatomic and functional abnormalities of the urinary tract are also associated with diabetes, and these abnormalities complicate UTI [10]. A Dutch study showed that despite the fact that patients with diabetes more often received longer and more potent initial treatment than patients without diabetes, women with diabetes more often had recurrences of their UTIs [11]. However, there is limited information on the prevalence and recurrence of UTI and genital infection among diabetes patients in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Anatomic and functional abnormalities of the urinary tract are also associated with diabetes, and these abnormalities complicate UTI [10]. A Dutch study showed that despite the fact that patients with diabetes more often received longer and more potent initial treatment than patients without diabetes, women with diabetes more often had recurrences of their UTIs [11]. However, there is limited information on the prevalence and recurrence of UTI and genital infection among diabetes patients in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…In older-age categories, girls received more anti-infective prescriptions, which accords with the findings of Majed and Moser, which showed that prescribing rates for antibiotics in young females (older than 4 years) were substantially higher than in males of the same age (24). The increase in the prevalence and average number of anti-infective prescriptions in girls in older-age categories could be explained by a higher frequency of urinary tract infections (7). Increased susceptibility of patients with diabetes to vulvovaginal candidiasis could be the reason for the increased number of anti-infective prescriptions, especially antimycotics, as was observed in the oldest girls (25).…”
Section: Discussionmentioning
confidence: 95%
“…The higher consumption of anti-infective medications in children and adolescents with type 1 diabetes corresponds with the more frequent occurrence of infections in these patients (7,8). It is possible that regular contact with the physician after the diagnosis of type 1 diabetes increased the probability of diagnosing different infections, which resulted in prescribing more anti-infectives for these children during the follow-up time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 According to a large Dutch study, 2 there is a high rate of recurrent UTIs in postmenopausal women (16.4%), rising to 19.1% in postmenopausal women with diabetes. The incidence in postmenopausal women is probably due to at least two factors: first, many postmenopausal women have urological issues such as incontinence, cystocele and postvoiding residual urine as a consequence of childbirth and loss of pelvic tone; and, secondly, low oestrogen levels YH Zhong, Y Fang, JZ Zhou et al…”
Section: Introductionmentioning
confidence: 99%